2015
DOI: 10.1007/s11130-015-0500-y
|View full text |Cite
|
Sign up to set email alerts
|

Growth Impairment Caused by Raw Linseed Consumption: Can Trypsin Inhibitors Be Harmful for Health?

Abstract: Linseed (Linun usitatissimum L.) is an important oilseed whose nutritional value can be impaired due to presence of antinutritional factors and low protein digestibility. Protein fractions from raw linseed meal were extracted, isolated and analyzed in vitro and in vivo. Globulins, the major protein fraction of linseed, showed low in vitro susceptibility to trypsin and chymotrypsin, but its in vivo digestibility was 93.2 %. Albumin fraction had high trypsin inhibition activity (5250 Inhibition Units g(-1)) and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
3
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 30 publications
0
3
0
Order By: Relevance
“…The Dicotyledonous plants like Quinoa, buckwheat and amaranth are considered as pseudocereals, rich in essential amino acids (Alvarez-Jubete et al, 2010) Seed: They include such as seeds such as flax, Chia, Sesame, Cucurbita, Watermelon, Musk seeds. It has been reported that Flax seeds and Chia seeds do not contain lysine (Anaya et al, 2015) whereas a high proportion of leucine and arginine is found in watermelon seeds (Kaul, 2011).…”
Section: Pseudocerealsmentioning
confidence: 99%
“…The Dicotyledonous plants like Quinoa, buckwheat and amaranth are considered as pseudocereals, rich in essential amino acids (Alvarez-Jubete et al, 2010) Seed: They include such as seeds such as flax, Chia, Sesame, Cucurbita, Watermelon, Musk seeds. It has been reported that Flax seeds and Chia seeds do not contain lysine (Anaya et al, 2015) whereas a high proportion of leucine and arginine is found in watermelon seeds (Kaul, 2011).…”
Section: Pseudocerealsmentioning
confidence: 99%
“…A significant finding is the presence of an item (1DWM_A) that forms part of a trypsin inhibitor. On the one hand, protease inhibitors are part of the natural defence of plants against harmful agents, which can be used biotechnologically or in plant protection [2,53], on the other hand, they can have adverse effects on human digestion and utilization of consumed proteins [54].…”
Section: Defence-and Stress-related Proteinsmentioning
confidence: 99%
“…The consumption of plant-derived food components increases continuously, and seeds are an important source that provides good quality of nutrition ( 30 ). Flaxseed, one of the richest sources of high-quality protein, also contains phenolic compounds, fibers, and essential amino acids; however, some studies argued that lysine is limiting in flaxseed ( 36 ). In their study, Lugo et al ( 37 ) observed that the composition of essential amino acids in chia lacks lysine, whereas the watermelon seeds were found to contain a good amount of leucine and arginine ( 38 ).…”
Section: Plant-based Sources and Demand Of Dietary Proteinmentioning
confidence: 99%
“…While valine helps in the coordination of motor cells, and aspartate and glutamate are essential for hormonal regulation and immunological stimulation, respectively ( 35 ). Leucine and isoleucine are assisting as building blocks of other proteins ( 36 ). Generally, it has been recommended that, for adults, the protein intake should be in-between 0.8 and 1 g/Kg body-weight/day ( 56 , 57 ).…”
Section: Plant-based Sources and Demand Of Dietary Proteinmentioning
confidence: 99%